PROFIL KEMAMPUAN PENALARAN INDUKTIF MATEMATIKA MAHASISWA PENDIDIKAN MATEMATIKA UNIPA DITINJAU DARI GAYA BELAJAR - Haryono, Agus; Tanujaya, Benidiktus (Journal of Honai Math, 2018)
Tkinesthetic learning style; problem solvinghe purpose of this research was to study the profile of students' mathematical inductive reasoning abilities regarding visual, auditory and kinesthetic learning styles in solving mathematical problems. The research method used is qualitative with a descriptive approach. The results of the study showed that UNIPA mathematics education students tended to study with Visual Learning Styles. Students with this learning style tend to have inductive mathematical reasoning abilities that are better than inductive mathematical reasoning abilities of students learning with auditorial learning styles and those who learn with the kinesthetic learning style. Also, Mathematics Education students of University of Papua do not have the ability to examine the validity of an argument and find patterns or characteristics of mathematical symptoms to generalize.Â DOI:Â https://doi.org/10.30862/jhm.v1i2.1049